Diversidade sexual na escola: um "problema" posto à mesa. - Joca, Alexandre Martins (2008)
This research is a paper about sexual educated education through the dialog between school and the homossexual movement in teaching continued formation about gender and sexual diversity, done by The Grupo de Resistência Asa Branca – GRAB, in 2007, with Fortaleza’s public schools’ educators. The dialog about the destruction of the meanings and senses attributed to the human sexuality, with the objective of facing the social unequalities born from homofobia directed to lesbians, gays, bisexuals, transvestites and transexuals – LGBTT. In this way, the present research debates the fragilities and the possibilities of the schools to the development of educative practice of recognizing and defense of the gender’s identity and of sexual diversity, in a way to comprehend its limits and to observe its opportunities. So, it is intended to contribute with the constitution of a sexual educated education on facing the homofobia, in the sense of thinking of educative practices, which provides positive social relationships with LGBTT in the school environment.